2018
DOI: 10.17645/mac.v6i2.1321
|View full text |Cite
|
Sign up to set email alerts
|

The Form of Game Formalism

Abstract: This article explores how the concept of formalism and the resulting method of formal analysis have been used and applied in the study of digital games. Three types of formalism in game studies are identified based on a review of their uses in the literature, particularly the discussion of essentialism and form that resulted from the narratology-ludology debate: 1) formalism focused on the aesthetic form of the game artifact, 2) formalism as game essentialism, and 3) formalism as a level of abstraction, relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…First of all, as Myers (2010) rightfully notes, Russian Formalism is 'one of the clearest and most influential statements of formalism in the arts' (p. 40) and has consequently been the one most explicitly taken up in our field (e.g. Chew & Mitchell, 2019;Mitchell, 2016;Mitchell, Kway, Neo, & Sim, 2020;Mitchell, Sim, & Kway, 2017;Myers, 2010;Pötzsch, 2017;Willumsen, 2018). Secondly, the approach provides a highly flexible toolkit capable of guiding research into form aspects without predetermining their relevance or their functioning.…”
Section: What Is Russian Formalism?mentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, as Myers (2010) rightfully notes, Russian Formalism is 'one of the clearest and most influential statements of formalism in the arts' (p. 40) and has consequently been the one most explicitly taken up in our field (e.g. Chew & Mitchell, 2019;Mitchell, 2016;Mitchell, Kway, Neo, & Sim, 2020;Mitchell, Sim, & Kway, 2017;Myers, 2010;Pötzsch, 2017;Willumsen, 2018). Secondly, the approach provides a highly flexible toolkit capable of guiding research into form aspects without predetermining their relevance or their functioning.…”
Section: What Is Russian Formalism?mentioning
confidence: 99%
“…In game studies, formalism has often been used as an all-embracing term covering a range of methodological and ontological approaches. Willumsen (2018), for instance, shows how formalism is used for three different approaches in game studies: an aesthetic game formalism identified with those scholars looking for a 'narrativeness' in games (cf. Murray, 1997); a game essentialism identified with those scholars interested in finding the 'gameness' in games (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some systems can be very economical (10 gameplay bricks, Djaouti, Alvarez, Jessel, Methel, & Molinier, 2008), while other approaches are incredibly expansive in scope (hundreds of concepts in Björk and Holopainen’s [2004] Patterns in Game Design and dozens in Juul’s [2016] inspection of tile-matching games). As Ea Christina Willumsen (2018) points out in a recent contribution, many examples of game formalism seek to achieve an ideal level of abstraction, “related to the need for a formal language that accounts for—and helps categorize—the specific elements of a system” (p. 140) while keeping a focus on the essential property that games are meant to be played. Björk and Lankoski (2015) recommend a meticulous formalist description of game content, acknowledging that some modern games are too large to be described with such a technique.…”
Section: Hacs Adventuresmentioning
confidence: 99%
“…156–157). What is more, though the author at several points levies a critique towards what is inaccurately called the ‘formalist’ strand of game studies (see Willumsen, 2018) for favouring rules or procedural systems as defining properties of games at the expense of other game components, some of the multimodal analyses present in the book unfortunately end up making a similar claim. One example is the analysis of a mod for The Elder Scrolls V: Skyrim , where – as pointed out even by the author – multimodal dissonance disappears over time and, crucially, through play .…”
mentioning
confidence: 99%